Vaginal discharge: recommended management in general practice. Issue 5 (4th March 2013) - Colver, Helen; Malu, Manoj
Abstract Vaginal discharge is usually physiological or caused by infection, and most cases can be treated in primary care. Our Drug review considers the choice of treatments available followed by a review of prescription data.